Method for efficiently solidifying carbon dioxide with low cost and large quantity by using tailing filling body
Through a two-step carbon sequestration process, the tailings treated with grinding and active excitation are combined with gelling materials to achieve efficient carbon sequestration and mechanical properties of tailings filling bodies, and solve the slow carbon sequestration activity and filling of tailings in the existing technology. The problem of excessive carbonization of the body.
Patent Information
- Application Number
- CN202411635352.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
When using tailings to cure carbon dioxide by using tailings, the carbonization reaction activity is slow, the amount of carbon sequestration is low, and the filler is prone to excessive carbonization after carbon dioxide is introduced, which affects the mechanical properties.
Using a two-step carbon sequestration process, the tailings are treated first through grinding and active excitation to form nano-calcium carbonate, and then mixed with the gelling material, filled into the mining goaf, and carbon dioxide is introduced for curing to achieve the second step of carbon sequestration. .
It significantly improves the carbon sequestration amount and mechanical properties of tailings filler, achieves low-cost, bulk and efficient carbon dioxide solidification, and has a simple process and no wastewater generation.
Smart Images

Figure CN119430766A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the resource utilization of solid waste and the application of low-carbon / negative carbon technology, belongs to the field of mining engineering, and specifically relates to a method for high-efficiency solidification of carbon dioxide in large quantities at low cost in tailings filling bodies. Background Art
[0002] Since the beginning of the Industrial Revolution, the concentration of greenhouse gases in the atmosphere has increased significantly, and the world is facing severe challenges brought by carbon emissions. Achieving carbon neutrality is a complex process, involving the adjustment of energy structure, industrial transformation, technological innovation and policy support.
[0003] Tailings are waste materials from mineral processing that have no recycling value under specific economic and technical conditions. Their large-scale storage not only wastes a lot of land resources, but also causes serious environmental pollution due to toxic substances such as heavy metals. The tailings pond built for the storage of tailings is a major source of debris flow with high potential energy.
[0004] At present, tailings are mainly used for filling underground goaf, re-extraction of valuable minerals, and making building materials. The use of specific tailings as carbon capture, utilization and storage (CCUS) materials in mine filling has great application potential, and is expected to turn mine pit backfill sites into "carbon reservoirs" to achieve low-cost, large-scale carbon fixation. However, there are still many technical problems in the realization of this process or technology: on the one hand, tailings rich in basic / ultrabasic rocks contain rich Ca / Mg silicate minerals, which have potential advantages in CO2 mineralization and storage, but their carbonization reaction activity is extremely slow in the natural mineralization process, and the carbon fixation amount is extremely low; on the other hand, when filling the underground goaf with the filling material prepared by tailings and cementitious materials, if carbon dioxide is directly introduced, it is easy to cause excessive carbonization of the filling body, affecting the mechanical properties of the filling body.
[0005] Some technical methods have also been published in relevant patent documents. For example, CN113213829B discloses a method for carbonization cementation filling of tailings, which uses solid waste with high calcium and magnesium content, low hydration activity, and difficult resource utilization as cementing material, greatly reducing the raw material cost of tailings cementation mining, and also solving the environmental protection problems such as land occupation and pollution caused by solid waste storage. And a large amount of CO2 can be fixed in carbonization maintenance, which is low-carbon and environmentally friendly. However, it only considers the carbon fixation of cementing materials in the filling body, and the carbon fixation potential of silicate minerals such as Ca / Mg in tailings with a mass fraction of more than 50% has not been explored, resulting in extremely low CO2 solidification, only about 1.23%. CN117365633B discloses a carbon dioxide filling method, which proposes two methods of direct mineralization and indirect mineralization to pump carbon dioxide filling materials into underground goafs, and provides a method for calculating the amount of carbon sequestration, as well as a method for calculating the carbon footprint and carbon consumption in the process of raw material transportation, filling slurry preparation, underground injection and filling. However, its direct carbonation method involves the carbonation of cementitious materials during the stirring process, which will inhibit the hydration process and affect the mechanical properties of the filling body; while the indirect mineralization method only considers the CO2 mineralization of the mineralized raw materials, ignoring the carbon fixation potential of the cementitious materials after hardening, and the process is relatively complicated and the cost is relatively high. Summary of the invention
[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for low-cost, large-scale and efficient carbon fixation in tailings filling bodies in view of the deficiencies in the prior art, so as to solve the above technical problems and achieve low-cost, large-scale, and efficient carbon fixation in tailings filling bodies.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for high-efficiency solidification of carbon dioxide in large quantities at low cost in tailings filling bodies comprises the following steps: (1) Grinding and screening the tailings raw materials, activating the tailings, and then adjusting the pH; (2) directly introducing carbon dioxide gas into the slurry formed in (1) under wet conditions to achieve the first step of carbon fixation of the tailings to obtain carbon-fixed tailings; (3) mixing the carbon-fixing tailings obtained in step (2) with the gelling material and the additive solution, adjusting the fluidity of the slurry, mixing and stirring the slurry evenly, and filling the slurry into the goaf of the mine to form the mine filling material; (4) After the filling material obtained in step (3) has been cured or hydrated for 3 to 28 days, carbon dioxide gas is introduced again so that the filling material is cured in an environment where carbon dioxide exists, thereby achieving the second step of carbon fixation and obtaining a carbon-fixed filling material with satisfactory mechanical properties and a high carbon fixation amount.
[0008] Furthermore, in step (1), the tailings raw material is basic or ultrabasic tailings, containing one or more of olivine, serpentine, pyroxene and feldspar.
[0009] Furthermore, in step (1), the tailings raw material is ground by a ball mill and then passed through a 200-mesh standard sieve with a pass rate of more than 90%.
[0010] Furthermore, in step (1), the activity stimulation is carried out using any one or more additives selected from the group consisting of alcohol amines, inorganic ammonium salts and small molecule amino acids. The additives are mixed with water to form a solution with a concentration of 0.2-1 mol / L (preferably 0.5 mol / L). The sieved tailings raw material powder is then mixed with the additive solution at a ratio of 400-600 g / L to form a slurry. The slurry is stimulated at 60-80°C for 8-12 hours, during which the slurry is kept in a stirred and flowing state.
[0011] Furthermore, in step (1), pH control is performed using 1-3 mol / L (preferably 2 mol / L) NaOH solution, and the pH value is controlled to be above 12.
[0012] Furthermore, in step (2), the first step of carbon fixation is carried out in a closed container, wherein the carbon dioxide gas is transported in a stable circulating airflow, and air stones are installed during the process to ensure that the carbon dioxide is evenly dispersed in the slurry. The concentration of the introduced carbon dioxide gas is 50-99%, so that the gas pressure in the closed container is controlled at 0.1-1 MPa.
[0013] Furthermore, in step (2), during the first step of carbon fixation, the slurry is heated to 60-80°C, and the carbon fixation reaction is carried out for more than 6 hours under stirring and intermittent ultrasonic conditions, with an intermittent ultrasonic power of 20-40 kHz, each ultrasonication lasting 15-30 minutes, and an interval of 10-20 minutes.
[0014] Furthermore, in step (3), the cementitious material is compounded from cement, slag, fly ash and steel slag powder, wherein, by weight, the cement is 20-60 parts, the slag is 30-70 parts, the fly ash is 10-20 parts and the steel slag is 1-10 parts; so that the filling body meets the mechanical properties and fillability requirements.
[0015] Furthermore, in step (3), the admixture is any one or more of a water reducer, a retarder and a foaming agent, and the dosage is 0.5-1%, 0.1-2% and 0.05-0.1% of the amount of the cementitious material, respectively; the cementitious material and the carbon-fixing tailings are mixed in a ratio of 1:4 to 8 of mortar-sand, and the amount of water used in the preparation of the filling body is calculated based on a slurry concentration of 65-75%.
[0016] Furthermore, in step (4), the curing conditions for the second step of carbon fixation are: temperature 20-40°C, pressure 0.1-1 MPa, relative humidity 55-85%, CO2 concentration of more than 50%, and curing for more than 24 h. Beneficial Effects
[0017] (1) The present invention uses tailings rich in basic / ultrabasic materials and filling cementitious materials to prepare mine filling materials, and realizes large-scale mineralization and storage of carbon dioxide in mine fillings through a "two-step carbon fixation" process. On the one hand, the tailings can be fully activated to ensure that they have carbon fixation capacity and fully increase the carbon fixation amount of the tailings filling body; on the other hand, the nano-calcium carbonate formed by its "first step of carbon fixation" not only plays a nucleation effect and a filling effect, but also promotes the hydration of the filling body cementitious materials, significantly improving the application performance of the filling body. In addition, the "first step of carbon fixation" uses intermittent ultrasonic technology to not only improve the contact ability between the activated tailings and the carbon dioxide interface, but also change the morphology of nano-calcium carbonate, further improving the application performance of the filling body. The use of tailings filling cementitious materials in conjunction with carbon dioxide in-situ filling / backfilling can achieve low-cost, large-scale and efficient filling, and the on-site filling technology transformation is simple and the effect is significant.
[0018] (2) The present invention uses an activating admixture to activate the carbonization activity of the tailings, making it easier for the Ca / Mg elements to react with CO2 in the liquid phase. At the same time, there is a large amount of silica gel in the activated tailings, which can achieve tailings activation and "first step carbon fixation". No wastewater such as leaching liquid or cleaning liquid is generated during the whole process. At the same time, the nano calcium carbonate formed by the "first step carbon fixation" of the tailings accelerates the hydration reaction rate of the cementitious material through its nucleation effect during the subsequent filling preparation and maintenance process. Its micro-aggregate and filling effect optimize and improve the application performance of the filling.
[0019] (3) The present invention uses carbon-fixing tailings and cementitious materials to prepare mine filling test blocks, which are then cured underground to a certain age and then introduced with carbon dioxide again, making full use of the "second step carbon fixation" of the hydration products of the cementitious materials in the mine filling body. In this process, the hydration products such as calcium hydroxide, magnesium hydroxide and CSH gel further react with CO2 to form a carbon-fixing filling body, thus achieving tailings disposal and CO2 coordinated in-situ filling. The 3-day compressive strength of the carbon-fixing filling body test block can reach more than 3 MPa, the 28-day compressive strength can reach more than 5 MPa, and the carbon fixation amount can reach more than 13 wt.%.
[0020] (4) The present invention aims to improve the various properties of the filling body by adding admixtures during the preparation of the filling body. Among them, the water reducer can effectively reduce the amount of water used in the preparation of the filling body, improve the flow properties of the filling body, and enhance its mechanical properties; the retarder helps to ensure the good transportation performance of the filling body in the mine filling pipeline, avoiding the effects of pipe blockage and insufficient filling; the application of the foaming agent can reduce the volume shrinkage of the filling body, increase the top connection rate of the filling body, and improve the filling efficiency and stability. At the same time, the porous structure can reduce the dead weight of the filling body, have a good blasting shock wave absorption effect, improve the safety of the mine, reduce the filling cost, and also help the diffusion of CO2 in the structure and increase the carbon fixation of the filling body.
[0021] (5) The present invention adopts accelerated wet carbonation technology, uses heating or intermittent ultrasonic technology or a method of coupling the two, and utilizes the ultrasonic cavitation effect to enhance the diffusion and mass transfer rate of the gas-liquid-solid three-phase two-interface multiphase reaction, effectively promoting the dispersion of CO2 and activated tailings during the carbonation process, and promptly eliminating the negative impact of the reduced mass transfer efficiency caused by the carbonization layer coating of the tailings particles. In addition, ultrasonic activation can also regulate the morphology of carbonate products, making their nucleation effect and micro-aggregate more obvious, thereby improving the application performance of mine filling bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0023] Figure 1 The following is a brief process flow chart of the present invention.
[0024] Figure 2 The XRD spectrum of the raw material copper-nickel tailings of the present invention.
[0025] Figure 3 The XRD spectra of Example 1 (a) and Example 2 (b) of the present invention before and after active activation of tailings carbonization.
[0026] Figure 4 The XRD spectra of the filling bodies at different ages before and after carbonization in Example 1 (a, a1) and Example 2 (b, b1) of the present invention are shown.
[0027] Figure 5 Thermogravimetric (TG) spectra of the filling body samples of Examples 1 (a), 2 (b), and 3 (c) of the present invention before and after carbonization.
[0028] Figure 6 These are SEM images of the filling body samples of Example 1 (a, a1) and Example 3 (b, b1) of the present invention before and after curing for 3 days and “second carbon fixation”.
[0029] Figure 7These are SEM images of the filling body sample of Example 2 of the present invention before and after the “second carbon fixation” after curing for 3 days (a, a1) and 28 days (b, b1). DETAILED DESCRIPTION
[0030] The present invention can be better understood with reference to the following examples.
[0031] The process flow of the tailings filling body of the present invention for high-efficiency and low-cost large-scale solidification of carbon dioxide can be found in Figure 1 As shown, the following steps are included: (1) Grinding and screening the tailings raw materials, activating the tailings, and then adjusting the pH; (2) directly introducing a stable circulating carbon dioxide gas into the slurry formed in (1) under wet process conditions and dispersing it with air stone to achieve the first step of carbon fixation of the tailings and obtain carbon-fixed tailings; (3) mixing the carbon-fixing tailings obtained in step (2) with the gelling material and the additive solution, adjusting the fluidity of the slurry, mixing and stirring the slurry evenly, and filling the slurry into the goaf of the mine to form the mine filling material; (4) After the filling material obtained in step (3) has been cured or hydrated for 3 to 28 days, carbon dioxide gas is introduced again so that the filling material is cured in an environment where carbon dioxide exists, thereby achieving the second step of carbon fixation and obtaining a carbon-fixed filling material with satisfactory mechanical properties and a high carbon fixation amount.
[0032] In the following examples, the carbon fixation amount is calculated by thermogravimetric (TG) testing method, and the calculation method is as follows:
[0033] in: ——The content of carbonized products in the sample after carbonization curing is quantitatively obtained by TG curve at 550-900 ℃. In order to accurately quantify, nitrogen needs to be introduced as a protective gas during thermogravimetric testing.
[0034] Table 1 shows the main chemical components of the copper-nickel tailings used in the following examples, in which the contents of MgO and Fe2O3 are relatively high, and a small amount of CaO and Al2O3 is contained. Figure 2 This is the XRD diagram of the tailings raw material. Its main mineral components include forsterite, serpentine and pyroxene, which are relatively common ultrabasic rock minerals.
[0035] Table 1 Main chemical components of copper-nickel tailings Example 1
[0036] A method for high-efficiency solidification of carbon dioxide in large quantities at low cost in tailings filling bodies comprises the following steps: (1) The copper-nickel tailings raw materials were ground through a 200-mesh sieve, and the tailings were reacted with 0.5 mol / L inorganic ammonium salt solution at 80 °C for 12 h. Finally, 2 mol / L NaOH was used to adjust the pH value to 12.4; (2) The slurry formed in (1) is directly introduced into a stable circulating carbon dioxide gas (with a concentration of more than 50%) under wet conditions, and is dispersed by using air stone so that the gas pressure in the closed container is controlled at 0.3-1 MPa. The slurry is subjected to accelerated carbonation at 80 °C for 6 h under stirring and intermittent ultrasonic conditions. The intermittent ultrasonic power is 30 kHz, and each ultrasonic treatment lasts for 20 min with an interval of 10 min to obtain a carbon-fixed tailing. (3) Weigh the carbon-fixing tailings obtained in (2) and the cementitious material in a ratio of 6:1, add 0.5% of the cementitious material amount of a water reducer and 0.08% of a foaming agent, and mix them evenly, wherein the cementitious material includes 20 parts of cement, 65 parts of slag, 10 parts of fly ash, and 5 parts of steel slag, and then add water to a slurry concentration of 65%, mix and stir, and obtain a mine filling body; (4) The filling body obtained in (3) was cured for 3 d and 28 d respectively, and then carbon dioxide gas was introduced and carbonized and cured for 24 h at a temperature of 30 °C, a pressure of 1 MPa, and a CO2 concentration of 99% to obtain a carbon-fixed filling body.
[0037] like Figure 3 The XRD patterns of the tailings in Example 1 before and after the "first step of carbon fixation" shown in (a) show that after carbonization, it can be found that there is obvious formation of the carbonization product magnesia calcite. The XRD patterns of the filling body in Example 1 before and after the "second step of carbon fixation" are as follows: Figure 4 As shown in (b, b1), it can be found that the peak of calcite already existed before carbonization curing (corresponding to the result of “first step carbon fixation”), while the peak of calcite was further enhanced after carbonization curing, and new carbonate peaks (such as aragonite and vaterite) were formed.
[0038] The microscopic morphology of the sample in Example 1 before and after the “second step carbon fixation” after curing for 3 days was analyzed by SEM. The results are as follows: Figure 6 (a, a1). It can be found that there are a large number of nanocubic calcite particles distributed in the hardened slurry before the "second step carbon fixation". They are the products of the "first step carbon fixation" of activated tailings, and they grow in large quantities as nucleation sites in the slurry. After the "second step carbon fixation" curing, the nanocalcite in the hardened slurry is converted into a short needle-rod-shaped calcium carbonate encapsulation structure. It is speculated that during the carbonization curing process of the "second step carbon fixation", the nanocalcite acts as a crystal nucleus, continues to undergo carbonation reaction, and grows into short needle-rod-shaped calcium carbonate, which improves the structural density and mechanical properties of the filling body. Example 2
[0039] A method for high-efficiency solidification of carbon dioxide in large quantities at low cost in tailings filling bodies comprises the following steps: (1) The copper-nickel tailings raw materials were ground through a 200-mesh sieve, and the tailings were reacted with 0.5 mol / L small molecule amino acid solution at 70 °C for 12 h, and finally the pH value was adjusted to 12 using 2 mol / L NaOH; (2) The slurry formed in (1) is directly introduced into a stable circulating carbon dioxide gas (with a concentration of more than 50%) under wet conditions, and is dispersed by using air stone so that the gas pressure in the closed container is controlled at 0.3-1 MPa. The slurry is subjected to accelerated carbonation at 80 °C, stirring and intermittent ultrasonic conditions for 8 h, with an intermittent ultrasonic power of 30 kHz, each ultrasonic treatment for 20 min, and an interval of 10 min to obtain a carbon-fixed tailing; (3) Weigh the carbon-fixing tailings obtained in (2) and the cementitious material in a ratio of 8:1, add 0.7% of the cementitious material water reducer and 0.2% of the retarder, and mix them evenly, wherein the cementitious material includes 50 parts of cement, 40 parts of slag, and 10 parts of fly ash, and then add water to a slurry concentration of 70%, mix and stir to obtain a mine filling body; (4) The filling body obtained in (3) was cured for 3 d and 28 d respectively, and then carbon dioxide gas was introduced and carbonized and cured for 36 h at a temperature of 35 °C, a pressure of 0.5 MPa, and a CO2 concentration of 75% to obtain a carbon-fixed filling body.
[0040] Example 2 The XRD patterns of tailings before and after the "first step of carbon fixation" are as follows Figure 3 As shown in (b), it can be found that small molecule amino acids have a poorer dissolution effect on olivine and serpentine in tailings than inorganic ammonium salts, but it can be found in the XRD after carbonization that they can significantly promote the formation of magnesite. And the XRD of the filling body prepared in Example 2 before and after the "second step carbon fixation" is as follows Figure 4 As shown in (a, a1), it can be clearly found that after carbonization curing, in addition to the obvious increase in the calcite peak, a magnesite peak also appeared. The microscopic morphology of the filling body sample of Example 2 before and after the "second step of carbon fixation" was observed by SEM, as shown in Figure 7 As shown, a large number of nano-calcite particles are formed in the hardened slurry before the "second step of carbon fixation", and the hydrated calcium silicate and calcite particles grow significantly in the sample after curing for 28 days. After the "second step of carbon fixation", the nano-carbonate particles grow significantly in the hardened slurry of the sample after curing for 3 days, and the calcite grows obviously in the sample after curing for 28 days, and the formation of dolomite can be clearly observed. Example 3
[0041] A method for high-efficiency solidification of carbon dioxide in large quantities at low cost in tailings filling bodies comprises the following steps: (1) The copper-nickel tailings raw materials were ground through a 200-mesh sieve, and the tailings were reacted with 0.5 mol / L inorganic ammonium salt solution at 75 °C for 10 h, and finally the pH value was adjusted to 13.1 with 2 mol / L NaOH; (2) The slurry formed in (1) is directly introduced into a stable circulating carbon dioxide gas (with a concentration of more than 50%) under wet conditions, and is dispersed by using air stone so that the gas pressure in the closed container is controlled at 0.3-1 MPa. The slurry is subjected to accelerated carbonation at 80 °C under stirring and intermittent ultrasonic conditions for 8 h. The intermittent ultrasonic power is 20 kHz, and each ultrasonic treatment lasts for 15 min with an interval of 15 min to obtain a carbon-fixed tailing. (3) Weigh the carbon-fixing tailings obtained in (2) and the cementitious material in a ratio of 6:1, add 0.5% of the cementitious material amount of a water reducer and mix them evenly, wherein the cementitious material includes 20 parts of cement, 65 parts of slag, 10 parts of fly ash, and 5 parts of steel slag, and then add water to a slurry concentration of 65% and mix and stir to obtain a mine filling body; (4) The filling body obtained in (3) was cured for 3 d and 28 d respectively, and then carbon dioxide gas was introduced and carbonized and cured for 24 h at a temperature of 25 °C, a pressure of 0.5 MPa, and a CO2 concentration of 99% to obtain a carbon-fixed filling body.
[0042] The microstructure of the sample in Example 3 before and after carbonization for 3 days was analyzed by SEM. Figure 6 As shown in (b, b1), the difference between Example 3 prepared by intermittent ultrasonic treatment of tailings and Example 1 prepared by heating treatment of tailings is that there are more obvious honeycomb CSH gel and calcium hydroxide in the structure. It can be seen that ultrasonic pretreatment can promote the hydration reaction of cementitious materials and contribute to the formation of hydration products, indicating that ultrasonic pretreatment is used for the "first step of carbon fixation" to effectively promote the dispersion of CO2 and activated tailings during carbonation, and timely eliminate the negative impact of the decrease in mass transfer efficiency caused by the carbonization layer coating of tailings particles, thereby significantly improving the microstructure of hardened slurry. After the "second step of carbon fixation", Example 3, due to the ultrasonic pretreatment effect, more active sites in the slurry are exposed, causing it to form more coarse rod-shaped carbonate mineralization products. Under the action of ultrasonic cavitation, nano calcium carbonate has significantly improved in morphology and production, with a more obvious nucleation effect and the effect of promoting the hydration reaction of cementitious materials, which improves the structural density and mechanical properties of the filling body.
[0043] Thermogravimetric (TG) analysis of the filling body samples of Examples 1, 2, and 3 before and after carbonization was performed. The results are shown in Figure 5It can be seen that there are two stages with faster mass loss rates, namely the decomposition of bound water and ettringite within 100°C, and the decomposition of carbonates within 550-900°C. The CO2 absorption of the filling body sample is calculated by the mass loss in the carbonate decomposition range and the carbon fixation calculation formula, and the obtained data is shown in Table 2. Comparative Example 1
[0044] The method for solidifying carbon dioxide in tailings of this comparative example comprises the following steps: (1) grinding the copper-nickel tailings raw material through a 200-mesh sieve, drying and setting aside to obtain tailings raw material that has not been chemically activated; (2) Weigh the tailings powder obtained in (1) and mix it evenly with a cementitious material in a ratio of 6:1, wherein the cementitious material includes 55 parts of cement, 25 parts of slag, 15 parts of fly ash, and 5 parts of steel slag, and then add water at a slurry concentration of 65% to mix and stir to form a carbon solid test block; (3) The filling body obtained in (2) was cured for 3 d and 28 d respectively, and then carbon dioxide gas was introduced to fix carbon. The filling body was carbonized and cured for 24 h at a temperature of 25 °C, a pressure of 0.8 MPa, and a CO2 concentration of 99% to obtain a carbon-fixed filling body. Comparative Example 2
[0045] The direct wet mineralization method in a carbon dioxide filling method in CN117365633B is used for carbon fixation, comprising the following steps: (1) Weigh a certain mass of tailings and water and introduce CO2 into a mixer to accelerate carbonation for about 6 h; (2) Weigh the cementitious material according to the ratio of mortar to sand of 1:6, wherein the cementitious material includes 100 parts of cement, add it into the mixer and stir it evenly at a slurry concentration of 65% to form a slurry; (3) The molded specimens were carbonized and cured after 3 and 28 days of curing to obtain carbon-fixed filling bodies. Comparative Example 3
[0046] The indirect mineralization method in a carbon dioxide filling method in CN117365633B is used to fix carbon, comprising the following steps: (1) The copper-nickel tailings were used as mineralization raw materials. The tailings were first leached with 0.5 mol / L hydrochloric acid solution for 10 h, and then carbon dioxide gas was directly introduced under wet conditions for 24 h. At the same time, 2 mol / L NaOH was used to control the pH value to be alkaline. (2) After the reaction is fully carried out, the slurry in (1) is precipitated and filtered, and the obtained carbon fixation product is used as fine aggregate for the preparation of filling materials; (3) The cementitious material and the carbon-fixing fine aggregate are mixed evenly at a mortar-sand ratio of 1:6, wherein the cementitious material includes 100 parts of cement, which are mixed in a mixer at a slurry concentration of 70% to obtain a filling body. Comparative Example 4
[0047] Considering the superior steps of the direct wet method and the indirect mineralization method in a carbon dioxide filling method in CN117365633B, an experimental design was combined on this basis, as comparative example 4, including the following steps: (1) The copper-nickel tailings were used as mineralization raw materials. The tailings were first leached with 0.5 mol / L hydrochloric acid solution for 10 h, and then carbon dioxide gas was directly introduced under wet conditions for 24 h. At the same time, 2 mol / L NaOH was used to control the pH value to be alkaline. (2) After the reaction is fully carried out, the slurry in (1) is precipitated and filtered, and the obtained carbon fixation product is used as fine aggregate for the preparation of filling materials; (3) Mixing the cementitious material and the carbon-fixing fine aggregate evenly at a mortar-sand ratio of 1:6, wherein the cementitious material includes 100 parts of cement, and mixing them in a mixer at a slurry concentration of 70% to obtain a filling body; (4) The molded specimens were carbonized and cured after 3 and 28 days of curing to obtain carbon-fixed filling bodies.
[0048] In order to verify the mechanical properties, carbon fixation performance and microstructure of the carbon fixation filling material prepared by the present invention, various properties of the carbon fixation filling materials prepared by Examples 1-3 and Comparative Examples 1-4 were tested. The specific results are shown in Tables 2 and Figure 2-7 .
[0049] Table 2 Performance of Examples and Comparative Examples
[0050] From the data in the above table, it can be found that Examples 1-3 all have good fluidity under the condition of a mortar-sand ratio of 1:4-8, and the compressive strength after carbonization curing can reach more than 3 MPa at the age of 3 days and more than 5 MPa at the age of 28 days. After a two-step carbon fixation method, the carbon fixation amount per unit mass of the carbon-fixing filler can reach 13 wt.% or more, and the process is simple, without any wastewater or other waste generated, and there will be no carbon dioxide leakage, etc. It can be found from the XRD and SEM images that in Examples 1 to 3, by activating the tailings with specific additives, the "first step of carbon fixation" of the tailings accounting for more than 50% of the mass fraction of the filling body is achieved, and a large amount of CO2 can be sealed in the tailings. The nano calcium carbonate structure formed can effectively act as a nucleation site. At the same time, the silica gel formed by the reaction can be used as active silica when preparing the filling body test block with the gelling material to promote the formation of hydration products such as CSH gel and improve the strength of the filling body; the "second step of carbon fixation" of the filling body sample can further fix CO2, and the generated calcium carbonate can be used as a nanomaterial to effectively improve the compactness and application performance of the filling body. In particular, the patent of this invention proposes intermittent ultrasonic technology for the first time in the "first step of carbon fixation", which improves the diffusion and mass transfer rate of the gas-liquid-solid three-phase two-interface multiphase reaction, effectively promotes the dispersion of carbon dioxide and activated tailings during carbonation, and promptly eliminates the negative impact of the decrease in mass transfer efficiency caused by the coating of the carbonized layer of the tailings particles. In addition, ultrasonic activation can also regulate the morphology of carbonate products, making their nucleation effect and micro-aggregates more obvious, thereby improving the density and application performance of mine fillings.
[0051] Among the samples prepared by the method in CN117365633B, in Comparative Example 2, since the mineralized raw materials were not stimulated to fix carbon during the direct wet mineralization process, the carbon fixation amount was extremely low, and the cementitious material participated in the carbonation reaction during the stirring process and inhibited the hydration reaction, which easily led to poor development of the mechanical properties of the filling body; while in Comparative Example 3, the indirect mineralization method was used, and the wet carbonization accelerated material was leached and separated. First, silica gel was not added to the filling cementitious material, resulting in a certain amount of solid waste, which was not conducive to the development of the filling performance; second, the carbon fixation product was used as aggregate, which lost the nucleation and hydration promotion effect of the carbonization product such as nanocarbonate, which was not conducive to the development of the filling performance; third, the filling body was not carbonized and cured, and the carbon fixation performance of the cementitious material in the filling body was not achieved, resulting in low carbon fixation in this method. Although Comparative Example 4 combines the direct wet method and the indirect mineralization method according to the patent publication number CN117365633B, and the mechanical properties and carbon fixation performance of the filling body are improved compared with Comparative Examples 2 and 3, there is still a large gap in filling body strength and filling body carbon fixation compared with Examples 2 and 3 of the ultrasonic technology proposed in this patent.
[0052] In summary, the present invention can fully and effectively stimulate the carbon fixation performance of tailings accounting for more than 50% of the tailings filling material through the "two-step carbon fixation" process, and the nano-calcium carbonate and silica gel formed in the process can further improve and optimize the application performance of the mine filling body. By further preparing the carbon-fixing filling material, the calcium / magnesium ions in the gelling material in the filling body are fully reacted with carbon dioxide to mineralize, so as to achieve tailings disposal and CO2 coordinated in-situ filling. At the same time, the addition of admixtures including water reducers, retarders and foaming agents can not only effectively improve the mechanical properties and carbon fixation performance of the filling body, but also improve the filling body's top connection rate, improve flow properties and reduce deadweight, improve the stability and safety of mine filling, and reduce filling costs. The patent content has a simple operating process, and is expected to achieve low-cost, large-scale carbon fixation, and prepare carbon-fixing filling materials with excellent mechanical properties, with good economic, environmental and social benefits.
[0053] The present invention provides a method and idea for a method for high-efficiency solidification of carbon dioxide in a large amount at low cost in tailings filling. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for high-efficiency solidification of carbon dioxide in large quantities at low cost in tailings filling, characterized in that: The steps include: (1) Grinding and screening the tailings raw materials, activating the tailings, and then adjusting the pH; (2) directly introducing carbon dioxide gas into the slurry formed in (1) under wet conditions to achieve the first step of carbon fixation of the tailings to obtain carbon-fixed tailings; (3) mixing the carbon-fixing tailings obtained in step (2) with the gelling material and the additive solution, adjusting the fluidity of the slurry, mixing and stirring the slurry evenly, and filling the slurry into the goaf of the mine to form the mine filling material; (4) After the filling material obtained in step (3) has been cured or hydrated for 3 to 28 days, carbon dioxide gas is introduced again so that the filling material is cured in an environment where carbon dioxide exists, thereby achieving the second step of carbon fixation and obtaining a carbon-fixed filling material with satisfactory mechanical properties and a high carbon fixation amount.
2. The method for high-efficiency solidification of carbon dioxide in large quantities with low cost in tailings filling according to claim 1, characterized in that: In step (1), the tailings raw material is basic or ultrabasic tailings, containing one or more of olivine, serpentine, pyroxene and feldspar.
3. The method for high-efficiency solidification of carbon dioxide in large quantities with low cost in tailings filling according to claim 1, characterized in that: In step (1), the tailings raw material is ground by a ball mill and then passed through a 200-mesh standard sieve with a pass rate of more than 90%.
4. The method for high-efficiency solidification of carbon dioxide in large quantities with low cost in tailings filling according to claim 1, characterized in that: In step (1), the activity is stimulated by using any one or more additives selected from the group consisting of alcohol amines, inorganic ammonium salts and small molecule amino acids. The additives are mixed with water to form a solution with a concentration of 0.2-1 mol / L. The sieved tailings raw material powder is then mixed with the additive solution at a ratio of 400-600 g / L to form a slurry. The slurry is stimulated at 60-80°C for 8-12 hours. During this process, the slurry is kept in a stirred and flowing state.
5. The method for high-efficiency solidification of carbon dioxide in large quantities with low cost in tailings filling according to claim 1, characterized in that: In step (1), pH control is performed using a 1-3 mol / L NaOH solution, and the pH value is controlled to be above 12.
6. The method for high-efficiency solidification of carbon dioxide in large quantities at low cost in tailings filling according to claim 1, characterized in that: In step (2), the first step of carbon fixation is carried out in a closed container, wherein the carbon dioxide gas is transported in a stable circulating gas flow. During the process, air stones are installed to ensure that the carbon dioxide is evenly dispersed in the slurry. The concentration of the introduced carbon dioxide gas is 50-99%, so that the gas pressure in the closed container is controlled at 0.1-1 MPa.
7. The method for high-efficiency solidification of carbon dioxide in large quantities with low cost in tailings filling according to claim 1, characterized in that: In step (2), in the first step of carbon fixation, the slurry is heated to 60-80°C, and the carbon fixation reaction is carried out for more than 6 hours under stirring and intermittent ultrasonic conditions, with an intermittent ultrasonic power of 20-40 kHz, each ultrasonication for 15-30 minutes, and an interval of 10-20 minutes.
8. The method for high-efficiency solidification of carbon dioxide in large quantities with low cost in tailings filling according to claim 1, characterized in that: In step (3), the cementitious material is prepared by mixing cement, slag, fly ash and steel slag powder, wherein, by weight, the cement comprises 20-60 parts, the slag comprises 30-70 parts, the fly ash comprises 10-20 parts and the steel slag comprises 1-10 parts.
9. The method for high-efficiency solidification of carbon dioxide in large quantities with low cost in tailings filling according to claim 1, characterized in that: In step (3), the admixture is any one or more of a water reducer, a retarder and a foaming agent, and the admixture amounts are 0.5-1%, 0.1-2% and 0.05-0.1% of the amount of cementitious material, respectively; the cementitious material and the carbon-fixing tailings are mixed at a ratio of 1:4-8 to the mortar-sand ratio, and the amount of water used in the preparation of the filling body is calculated based on a slurry concentration of 65-75%.
10. The method for high-efficiency solidification of carbon dioxide in large quantities at low cost in tailings filling bodies according to claim 1, characterized in that: In step (4), the curing conditions for the second step of carbon fixation are: temperature 20-40 °C, pressure 0.1-1 MPa, relative humidity 55-85%, CO2 concentration of more than 50%, and curing for more than 24 h.
Citation Information
Patent Citations
A method for backfilling carbonized tailings
CN113213829B
A method for filling with carbon dioxide
CN117365633B
Cited By
Comprehensive utilization method and application of lead-zinc tailings
CN120398450A
Preparation method of carbon sequestration building material through carbon dioxide foaming storage and low-pressure forming
CN120794687A
Method and device for realizing carbon sequestration of red mud under supercritical condition
CN120903536A
Method and device for realizing carbon sequestration of red mud under supercritical conditions
CN120903536B
Method for preparing building material from asbestos tailings
CN121800444A